2016
DOI: 10.1155/2016/6943053
|View full text |Cite|
|
Sign up to set email alerts
|

Cytoprotective and Cytotoxic Effects of Rice Bran Extracts in Rat H9c2(2‐1) Cardiomyocytes

Abstract: This study was aimed at preliminarily assessing the cytoprotective and antioxidative effects of rice bran extracts (RBEs) from a Sarawak local rice variety (local name: “BJLN”) and a commercial rice variety, “MR219,” on oxidative stress in rat H9c2(2-1) cardiomyocytes. The cardiomyocytes were incubated with different concentrations of RBE and hydrogen peroxide (H2O2), respectively, to identify their respective IC50 values and safe dose ranges. Two nonlethal and close-to-IC50 doses of RBE were selected to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Rice bran is a functional food that has been recognized as globally accessible, but not well known as food that can prevent and control chronic diseases [15,16]. Bioactive food components from rice bran were identified for cancer protective functions related to energy metabolism [1719], antioxidant [20], and direct anti-neoplastic activity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Rice bran is a functional food that has been recognized as globally accessible, but not well known as food that can prevent and control chronic diseases [15,16]. Bioactive food components from rice bran were identified for cancer protective functions related to energy metabolism [1719], antioxidant [20], and direct anti-neoplastic activity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrates that pre‐treatment with bran extract for 14 days showed improvement in oxidative stress markers such as MDA, NO, and HP and antioxidant enzyme activities suggesting its potent antioxidant activity. Recent in‐vitro study (Tan et al, ) showed an improved level of expression of antioxidant enzymes activity in rats heart cells on rice bran extract pre‐treatment against H 2 O 2 exposure. Relevant studies associated with rice bran aqueous‐ethanol extracts reported to have antioxidative properties (Jimenez‐Del‐Rio et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fermented rice bran extract was shown to inhibit ROS generation in cultured adipocytes subjected to H 2 O 2 -induced oxidative stress [ 42 ]. Further, pre-treatment with rice bran extract on rats’ heart cells exposed to H 2 O 2 was also found to increase both the activity and the level of expression of antioxidant enzyme catalase [ 43 ]. Such studies confirm the above in vitro studies regarding the inhibitory effect of rice bran intake on ROS production in cancer cell lines.…”
Section: Evidence For the Anti-oxidative Effects Of Rice Branmentioning
confidence: 99%